Co-Combustion of Coal and Biomass: Heating Surface Slagging and Flue Gases; Fire; Vol. 8, iss. 3 - Zhuykov A. V. Andrey Vladimirovich; Glushkov D. O. Dmitry Olegovich; Pleshko Andrey Olegovich A. O.; Grishina I. I. Irina Ivanovna; Chicherin S. V. Stanislav Viktorovich (2025, 2025)
Title screen